Unintentional weight loss in older adults : nutrition-related knowledge, perceptions and practices of nursing staff working in long-term care facilities in the Cape Metropole - De Haas, Johanna Cornelia (Stellenbosch : Stellenbosch University, 2016)
Thesis (MNutr)--Stellenbosch University, 2016.